Architecture of urban pavements. Multi-scale and digital methods for an ecological transition - Spartaco Paris; Elisa Pennacchia; Carlo Vannini (Agathón)
The management of large cities’ road infrastructure is increasingly complex, requiring tools and approaches continuously updated; these drive the governance to define specific solutions capable of being adapted to the variety of urban settings, guarantee renewed performance and contribute towards the pursuit of the objectives of environmental sustainability. This article aims to propose a multi-scale and interdisciplinary methodological approach based on digital tools aimed at defining requirements and strategies to promote widespread urban road regeneration. This approach has been applied to the city of Rome: the result is an operative tool to identify solutions to improve the urban quality of public spaces' vehicular, bicycle, and pedestrian street pavement.